Anion sensing porphyrin functionalized nanoparticles - Cormode, D; Davis, J; Beer, P (2008)
Disulfide and dithiocarbamate functionalized porphyrins have been synthesized and used as protecting ligands for gold nanoparticle formation either via ligand substitution reactions or by direct synthesis. These nanoparticles have been shown to recognize anions via changes in the absorbance spectrum of the surface adsorbed porphyrin moieties. Association constants, derived from quantitative titrations, indicate a remarkable surface enhancement effect where the surface bound porphyrins bind anions much more strongly than the free receptor in solution. © 2007 Springer Science+Business Media, LLC.